2019
DOI: 10.1097/bpb.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiological outcomes following single-stage treatment using external fixator, copious bone grafting and high dose antibiotics for infected postosteomyelitic nonunion of femoral shaft

Abstract: We aimed to study clinical and radiological outcomes following a ‘single-stage protocol’ in postosteomyelitic-infected nonunion of the femur in children. The report is based on a retrospective chart review (2010–2018) of 10 children below 12 years of age presenting with nonunion following a pathological fracture after osteomyelitis of hematogenous origin treated with above-mentioned operative modality. All patients were grade A (normal host) on the basis of the physiological classification. Patients with postt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The combined tibial and fibular harvesting as described in our series, although being a known procedure, has scantly been elucidated in literature [5–7]. Our series on such 16 dual harvests showed that tibial healing proceeded unhindered being an incomplete window-type resection (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The combined tibial and fibular harvesting as described in our series, although being a known procedure, has scantly been elucidated in literature [5–7]. Our series on such 16 dual harvests showed that tibial healing proceeded unhindered being an incomplete window-type resection (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The combined harvests, however, sum up as a major surgical procedure and require postoperative immobilization in a cast [5]. Postprocedure, the clinician’s focus is largely restricted to primary site outcome [6,7]. The overall impact of harvests on donor legs largely remains undocumented and therefore, formed the basis of the present research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Application of mono lateral external fixator for femoral bone transport to manage these cases has rarely been assessed in the literature with only seven studies found in the last 10 years with a limited number of cases. (3)(4)(5)(6)(7) This study hypothesizes that managing these injuries by mono lateral external fixator provides good to excellent radiological and functional outcomes.…”
Section: Introductionmentioning
confidence: 96%